Title of government spending and economic disaster theory in Post Asian Financial Crisis in 1997 & Global Financial Crisis 2008 impact on Malaysia / Mohd Azlan Abdul Majid ... [et al.] - Abdul Majid, Mohd Azlan; Pardi, Faridah; Kholib Jati, Muhammad Khodri; Hasan, Suzana (UiTM Cawangan Negeri Sembilan, 2022)
This research intents to investigate the Economic Disaster Theory of the past of recent shocks to Malaysia in the Asian Financial Crisis in 1997 and compare it to the Global Financial Crisis in 2008 by testing the economic disaster theorem. From the historical economic argument from the Classicism school of thought in Adam Smith to the Modern Keynesian model, fiscal policy's importance is vital in controlling and mitigating business cycles effect and economic downturn. The case arises with a focus on investigating Economic Disaster theory and comparing it with two shocks' impact in Malaysian cases. We take the data from 1974 to 2020 and use simple time series, Cholesky decomposition and time series method. As in Economic Disaster Theorem, the theory states that consumption and government will have a positive relationship during shock time. At the same time, investment and net export will negatively impact income. This is because the government is the only institution that can react in an ad hoc period. If the Malaysian cases shock economics disaster theorem hold, this will reflect the rejoice of the Keynesian tenet and support the J-Curve relationship. The output shows that long-run ARDL (Autoregressive Distributed Lags Model) partially supports the economic disaster theorem while the Cholesky impulse shows supported economic disaster theorem. Government Spending is a powerful tool, and this study proves the importance of the New Keynesian tenet.